Uncertain pathways: foundation skills tutors and marginalised students in neoliberal times. Issue 7 (3rd October 2018) - Strauss, Pat; Hunter, Judy
Abstract: This article deals with the work of polytechnic tutors on adult foundation programmes and describes how their work has been affected by the current neoliberal climate in the education sector. Inclusive neoliberalism is characterised by heightened regulation, reduced support for the public sector and a greater requirement for individual responsibility. The push to improve skills to meet labour demand is promoted as addressing social needs. Policies devised to promote these neoliberal values have led to numerous and far-reaching changes in adult education. In this study 73 foundation skills educators drawn from 8 institutions were interviewed to gain their insights into the effects of these policies. The article discusses three types of detrimental effects: the growing distrust between teaching staff and management; unsettling changes to institutional policy and its effects on staffing issues; and threats to the professionalism of teaching staff, the delivery of foundation studies, and the students themselves. Finally, the article suggests alternative possibilities for addressing these issues.